Experimental evaluation of thermal performance of two different finned latent heat storage systems. (October 2020) - Hassan, Ayad K.; Abdulateef, Jasim; Mahdi, Mustafa S.; Hasan, Ahmed F.
Abstract: Enhancing the reliability and acceptability of solar-based thermal energy system requires efficient thermal storage to enable the storage of surplus energy collected during day time for use during non-day light hours. However, most phase change materials (PCMs) used with thermal storages suffer from low thermal conductivity. Fin geometry has a major impact on the heat transfer rates of thermal storage. For this purpose, a comparative thermal performance assessment during charging is achieved for a shell-and-tube-type latent heat storage unit (LHSU) using different fin geometries. An experimental analysis is conducted on three LHSU geometries: non-finned LHSU, longitudinal finned (LF) LHSU (LF-LHSU) and circular finned (CF) LHSU (CF-LHSU). In addition, a visual observation of liquid fraction fronts is applied to confirm the completion of phase change cycles. Experimental results showed that the total charging time reduced by up to 70% and 55% using CF-LHSU and LF-LHSU, respectively. In comparison with the non-finned LHSU, the highest cumulative energy stored enhancement using CF-LHSU was approximately 52%. The experimental comparative assessment suggests that CF-LHSU provides improved charged thermal load operations by a factor of 1.2 as compared with LF-LHSU.